2021
DOI: 10.3389/fnut.2020.616484
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Food Texture Acceptance in 4- to 36-Month-Old French Children: Findings From a Survey Study

Abstract: Food texture plays an important role in food acceptance by young children, especially during the complementary feeding period. The factors driving infant acceptance of a variety of food textures are not well-known. This study summarizes maternal reports of children's ability to eat foods of different textures (here: acceptance) and associated factors. Mothers of 4- to 36-month-old children (n = 2,999) answered an online survey listing 188 food-texture combinations representing three texture levels: purees (T1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…The finding that across all AGs, textures such as dissolvable , soft and soupy / liquidy were tried by most infants, while rubbery , hard, and leafy were tried by substantially fewer infants, corroborates other reports ( 1 , 14 , 19 ). Indeed, dal water and rice water, both of soupy / liquidy texture, have been reported as the first complementary foods and are characterised by a thin consistency ( 30 ).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The finding that across all AGs, textures such as dissolvable , soft and soupy / liquidy were tried by most infants, while rubbery , hard, and leafy were tried by substantially fewer infants, corroborates other reports ( 1 , 14 , 19 ). Indeed, dal water and rice water, both of soupy / liquidy texture, have been reported as the first complementary foods and are characterised by a thin consistency ( 30 ).…”
Section: Discussionsupporting
confidence: 85%
“…However, this contrasts with reports indicating that many children under 6 months consume other liquids, such as plain water (10%), other milk (8%), or complementary foods (11%) in addition to breast milk; 96% of the study cohort had a history of breastfeeding, either in the past or at present. This is higher than the 62.9–91% reported for Western populations ( 14 , 19 ). Overall, the proportion of texture-sensitive children in our study was 67%, which is substantially higher than the 23% reported by the US population ( 22 ).…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations